Seguimento longitudinal do crescimento de prematuros com peso de nascimento menor de 1.500 gramas - Rover, Milene de Moraes Sedrez (2015)
The increasing survival of preterm infants with birth weight below 1500 grams (VLBW) determines the need for a focus on care and follow-up of this group after discharge from the Neonatal Intensive Care Unit (NICU). Based on the high morbidity rate and changes in the growth of these children, the growth follow-up of the VLBW preterm is turned into an essential tool for monitoring its health. Thus, this study aims to: evaluate the growth of the VLBW preterm from birth to 12 months of Corrected Age (CA) after the NICU s discharge; describe the Z score profile of the anthropometric variables from birth to 12 months of CA; identify events that have influenced the Extra Uterine Growth Restriction (EUGR) during hospitalization and in the 12 month period of follow-up; identify the morbidities that have influenced the growth of the VLBW preterm. It is a quantitative, observational, longitudinal, retrospective and cross sectional study, which was realized in High Risk Follow up Ambulatory. The study enrolled 71 children who were attended between 2006-2013, with birth weight below 1500 g; admitted to the NICU at birth and had at least three outpatient visits in the following periods: period I up to 3 months of CA; period II between 4-6 months of CA and period III between 7-12 months of CA. In order to classify the relation Weight/Gestational Age (GA) the Fenton and Kim s curve was used. Besides, to calculate the Z score, the Research Bulk Calculator and the Anthro calculators were used. The variables were analyzed by logistic regression with XLSTAT program. The GA average was 29.4 weeks; 36 (51%) PT male, 50 (70%) PT babies the weight was Appropriate for GA (AGA). During hospitalization, 43 (61%) babies used Parenteral Nutrition. The weight score Z average at birth was -0.95; at the hospital discharge -3.05; in period I -2.4; period II -1.8; period III -1.2. The height at birth was -1.21, at discharge -2.23; -2.5, -1.8 and -1.1 for the periods I, II and III, respectively. Regarding the Head Circumference (HC): Z score at birth was -0.71; at discharge -1.5; and monitoring -1.1, -0.8 and -0.5, respectively in the periods I, II and III. Presenting AGA birth weight, shorter hospitalization and percentage of lost weight during the hospitalization, reduce the chance for EUGR. In the follow up period, the occurrence of metabolic bone disease, retinopathy of prematurity, gastro esophageal reflux and hospitalization, increase the EUGR chance. Despite of the substantial reduction in the Z score during hospitalization, there was a progressive improvement during follow up in this score in the three anthropometric variables, especially in the HC. At 12 months of CA 86% of infants were with Z score above -2 in relation to HC. Thus, it was possible to verify the importance of nutrition in the neonatal period, as well as, the proper and systematic follow-up in order to minimize the consequences and changes in the growth caused by prematurity, focusing on the full potential of preterm.